Current best practice in the management of hypertensive disorders in pregnancy - Townsend, Rosemary (Integr Blood Press Control, 2016)
Preeclampsia is a potentially serious complication of pregnancy with increasing significance worldwide. Preeclampsia is the cause of 9%–26% of global maternal mortality and a significant proportion of preterm delivery, and maternal and neonatal morbidity. Incidence is increasing in keeping with the increase in obesity, maternal age, and women with medical comorbidities entering pregnancy. Recent developments in the understanding of the pathophysiology of preeclampsia have opened new avenues for prevention, screening, and management of this condition. In addition it is known that preeclampsia is a risk factor for cardiovascular disease in both the mother and the child and presents an opportunity for early preventative measures. New tools for early detection, prevention, and management of preeclampsia have the potential to revolutionize practice in the coming years. This review presents the current best practice in diagnosis and management of preeclampsia and the hypertensive disorders of pregnancy.